Main aspects of human resources management at the regional level (Economics and region, 2023)
The article examines the issue of human resources management at the regional level, in particular, it reveals what models exist and what model of human resources management in the field of public administration in Ukraine and its features. The study of the evolution of human resources management shows that the study of this issue goes from the study of the use of labor resources through personnel administration to personnel management, and later - human resources management. The concept of "human resources management" conveys a broader meaning than the concepts of "personnel management" or "personnel management", because the concept of "human resources management" means the application of a series of actions that are required to create productive relations of cooperation between employees of the organization. In contrast to traditional approaches to personnel management, human resource management considers the issue of management in a broader sense, as the strategic development of the organization, the main goal of which is not only to increase work efficiency, but also to promote the self-realization of each employee. The effective use of human resources in the system of regional government involves the implementation of a whole set of measures using the tools of regulatory, organizational, motivational, and communication mechanisms of state administration, which will allow providing authorities with highly qualified personnel, creating a rational system of management of various structures in the context of coordinating their activities for implementation state regional policy and regional development. The main functions of human resources management in the system of regional administrative institutions were also noted, namely: planning, selection (hiring), socialization, professional and career development, evaluation of performance indicators, motivation, support of labor relations for maximum use of the potential of human resources. The importance of human resources management for state authorities, in particular, at the regional level, is emphasized. The management of human resources in the system of regional government has its own characteristics, problems and requires the provision of professional development of human resources in the public service under special programs, strategic management of human resources, project approach, application of modern technologies of personnel management, implementation of the latest information and communication technologies of human resources management.
Keywords: human resources; human resources management; personnel management; regional level; personnel